STUDY OF THE EFFECT OF ULTRAFINE PARTICLE SIZE AND FROTHER TYPE VARIATION ON COPPER GRADE AND RECOVERY IN CLEANER FLOTATION CIRCUIT AT PT AMMAN MINERAL NUSA TENGGARA - Mahramuna, Desri
PT Amman Mineral Nusa Tenggara (PT AMNT) is one of the companies engaged in mining and mineral processing in Indonesia. PT AMNT operates in the mining and processing copper ore with the final product in the form of copper concentrate produced from the flotation process. Based on data on the overall circuit, there is a decrease in copper recovery in ultrafine particles (<10 microns). This size is too small, which can inhibit the flotation process due to the inhibition of interaction between air bubbles and particles. The ultrafine particles that fail to be recovered in the flotation process will be carried to the final tail with a relatively high copper content that can be increased again. In this study, experiments were conducted to determine the effect of ultrafine ore particles from the flotation cleaner circuit on copper content and recovery and flotation experiments involving variations in frother type to increase copper recovery to produce ultrafine particles in the PT AMNT flotation cleaner circuit. This study was divided into two experimental stages. The first stage of the experiment began with the sampling of four streams in the cleaner circuit including Polishing Mill Product (PMP) and Regrind Mill Product (RMP) as feed, Cleaner Scavenger Tail (CST) as tailings, and Final Concentrate (FC) as concentrate. The samples were then subjected to wet sieving, homogenization and splitting, Particle Size Distribution (PSD) determination, and content testing with Atomic Absorption Spectroscopy (AAS). The second stage of the experiment began with sampling the Cleaner Scavenger Tail (CST) stream. The samples were subjected to bulk flotation with three variations of frother types, namely no frother, weak frother, and strong frother. The flotation results were wet sieved, followed by homogenization and splitting, determination of Particle Size Distribution (PSD), and testing the content of each fraction with Atomic Absorption Spectroscopy (AAS). From the results of the first stage of research, it is known that the presence of ore particles <10 microns (ultrafine) in the cleaner flotation circuit has an effect in the form of a 15% decrease in copper recovery with high Cu levels in the ultrafine size fraction in the RMP (4.19%) and CST (4.02%) streams. In the second stage of the experiment, the overall copper recovery in the variations no frother, weak frother, and strong frother were 24.86%; 19.12%, and 19.21%, respectively. In the second stage of the study, it was found that the treatment of frother-type variation had a less significant impact on the ultrafine size copper recovery. However, adding frother is still needed in the flotation process of coarser ore particles at >10 microns in size.